PEMBROLIZUMAB - REVIEW OF USE AND EFFECTIVENESS IN THE TREATMENT OF SELECTED NEOPLASM - Konrad Kulka,; Wiktoria Król,; Zuzanna Kafara,; Donata Kowalczyk,; Zuzanna Lechowska,; Agnieszka Kafara,; Rafał Szarek,; Julia Koronczok-Matusiak,; Katarzyna Michta,; Dominika Jurczak, (International Journal of Innovative Technologies in Social Science, 2025)
The growing number of oncological patients worldwide pushes the need to research new possibilities in cancer treatment. Cancer cells use various mechanisms to avoid destruction. One of them is the PD-1/PD-L1 pathway which is used by neoplasm cells to inhibit immune response from T-cells. Pembrolizumab, a monoclonal antibody, is targeted against PD-1 receptors, therefore enhances anti-cancer T-cell activity by disabling PD-1/PD-L1 interaction. This study summarizes the current state of knowledge on clinical usefulness and efficiency of pembrolizumab monotherapy, therapy combined with chemotherapy and perioperative use  in melanoma, non-small cell lung cancer, pleural mesothelioma, classic Hodgkin lymphoma, urothelial cancer, head and neck squamous cell carcinoma, renal cell carcinoma, high-level microsatellite instability (MSI-H) or demismatch repair deficiency (dMMR) neoplasm, esophageal cancer, triple negative breast cancer, endometrial cancer, cervical cancer, adenocarcinoma of the stomach or gastroesophageal junction and bile duct cancer. Patients who received pembrolizumab during clinical trials had longer median overall survival and progression free survival rates than patients in placebo groups. Higher expression levels of PD-L1 on tumor cells correlated with greater clinical response, however pembrolizumab therapy was also beneficial in patients with lower expression levels.